2020
DOI: 10.1186/s13071-019-3862-4
|View full text |Cite
|
Sign up to set email alerts
|

Bovine ticks harbour a diverse array of microorganisms in Pakistan

Abstract: BackgroundTicks and tick-borne pathogens (TTBP) are a major constraint to livestock production in Pakistan; despite a high prevalence of TTBPs, knowledge on the capacity of Pakistani ticks to carry pathogens and endosymbionts is limited. Furthermore, mixed infections with multiple microorganisms further complicate and limit the detection potential of traditional diagnostic methods. The present study investigated the tick-borne microorganisms in bovine ticks in Pakistan, employing a high-throughput microfluidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
276
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 213 publications
(299 citation statements)
references
References 69 publications
19
276
4
Order By: Relevance
“…Finding ticks that carry DNA of up to seven microorganisms of veterinary and medical significance indicates the level of risk associated with tick infestation to animals as well as humans. Previously, a similar level of co-occurrence of endosymbionts (i.e., Francisella-like and Coxiella-like) and pathogens (belonging to Anaplasma, Babesia, Bartonella, Borrelia, Ehrlichia, Hepatozoon, Rickettsia and Theileria genera) in bovine ticks was reported from the Punjab and Sindh provinces of Pakistan [28]. Similarly, microbiome analyses of Dermacentor silvarum and Ixodes persulcatus ticks from China revealed the presence of up to 29 and 373 bacterial genera, respectively, belonging to endosymbionts and pathogens [68,69].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Finding ticks that carry DNA of up to seven microorganisms of veterinary and medical significance indicates the level of risk associated with tick infestation to animals as well as humans. Previously, a similar level of co-occurrence of endosymbionts (i.e., Francisella-like and Coxiella-like) and pathogens (belonging to Anaplasma, Babesia, Bartonella, Borrelia, Ehrlichia, Hepatozoon, Rickettsia and Theileria genera) in bovine ticks was reported from the Punjab and Sindh provinces of Pakistan [28]. Similarly, microbiome analyses of Dermacentor silvarum and Ixodes persulcatus ticks from China revealed the presence of up to 29 and 373 bacterial genera, respectively, belonging to endosymbionts and pathogens [68,69].…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, most of the families in the FATA are living with their animals and there is a general lack of awareness about TBDs of veterinary and public health importance [7]. Our findings and previous reports of rickettsial species from ticks in Pakistan [28] highlight the need to establish a diagnostic surveillance system for zoonotic rickettsial pathogens in this country.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A. marginale has previously been reported in Rh. microplus in Côte d'Ivoire [60], Ecuador [77], India [78] and Pakistan [79]. As for genus Ehrlichia, we recorded for the first time two different genotypes of "E. rustica" in both Rh.…”
Section: Discussionmentioning
confidence: 84%
“…Farmers did not perceive tick-borne pathogens as a threat (in contrast to AHPs) to their animals, although anaplasmosis, babesiosis and theileriosis are endemic bovine tick-borne diseases (TBD) in Pakistan (83). Recent investigations have demonstrated that bovine ticks carry a diverse array of pathogens, some of which can be zoonotic (84). Losses due to TBDs could be very high in Pakistan, particularly on resource-poor farms.…”
Section: Discussionmentioning
confidence: 99%